(untitled) (Nigerian Journal of Technology, 2016)
Load forecasting guides the power company to make some decisions on generation, transmission and distribution of electrical power. This work presents a solution methodology, using fuzzy logic approach for short term load forecasting (STLF) for Adamawa State University, Mubi. The proposed methodology utilized fuzzy reasoning decision rules that use the nonlinear relationships between inputs and outputs. The fuzzy logic model was developed in the Simulink environment of a MATLAB software. The model developed was able to forecast a day ahead load (kW) with a mean absolute error (MAPE) of 6.17% and it was observed that weather parameter (temperature) has significant impact on electrical load. http://dx.doi.org/10.4314/njt.v35i3.14